Manajemen Kurikulum Berbasis Madrasah Di MTs Bahrul Ulum Gadingmangu Perak Jombang - Beny Sintasari; Nuzulul Fitria (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) IAI Al Urwatul Wutsqo - Jombang, 2021)
This research to analyze and describe the planning, implementation, and evaluation of the madrasa-based curriculum at MTs Bahrul Ulum Gadingmangu Perak Jombang. The method used in this research is descriptive qualitative, with the type of field study research. For data collection techniques through interview techniques, observation, and documentation. Meanwhile, to check and examine data from various data collection techniques and existing data sources, the researchers used source triangulation techniques. The results of the research found are: (1) Madrasa-based curriculum planning begins with a meeting at the beginning of the school year and the formation of a curriculum development team. Curriculum planning refers to curriculum components, among others, determining curriculum objectives in accordance with the madrasa's vision and mission, determining learning content or materials, learning processes (methods), learning evaluations carried out by written tests and oral tests, (2) Implementation of a curriculum-based Madrasahs are divided into two parts, namely the implementation of the madrasa level curriculum who is responsible for the madrasah principal and the implementation of the class level curriculum is the responsibility of the educator, (3) Madrasa-based curriculum evaluation is carried out by evaluating the level of curriculum achievement, evaluating the performance of educators related to the implementation of the curriculum at the classroom level and assessment of student learning outcomes.